Managing Biological Risks in Biomedical laboratories of Public Hospitals in Athens, Greece, based on the Biosafety requirements - Vourtsis, Dionysios; Papageorgiou, Efstahia; Kriebardis, Anastasios; Karikas, George Albert; Willigen, Gijsbert van; Kotrokois, Kostantinos; Dounias, Georgios; Karkalousos, Petros (European Scientific Journal, ESJ, 2024)
Objectives: The aim of the present study was to review the laboratory workers’ perception on the biological risks in Biomedical laboratories of Public Hospitals in Athens, Greece, to evaluate how they are managing the biological materials and to propose mitigation measures according to the existing risk, the local legislations and the international Biosafety guidelines. Materials and Methods: The study was designed as a cross-sectional study with a detailed health and safety (H&S) questionnaire focused on biosafety and biorisk management. A total of 36 biomedical laboratories Biosafety Level-2 in 20 public hospitals were assessed for their biosafety containment and compliance with biosafety practices. Laboratory staff (medical laboratory doctors, medical laboratory technologists, laboratory assistants, biologists and biochemists) (n = 415) completed the questionnaire. Results: The results showed, that a significant percentage of laboratories lacked proper management of the biological agents and biological materials in general, thus more specific: restricted access 48.9%, controlled and independent ventilation 36.6%, use of BSCs 31.8%, biorisk management system in place 31.6%, risk assessments 28.4%, biosafety manuals 21.4%, SOPs 35.9%, assigned biosafety officers 10.8%, occupational Doctor 34.9%, accidents reporting 25.5%, emergencies plan 34.2% and biosafety training programs 28.2%. Conclusion: There are marked deficiencies in containment and administrative controls, as well as in the implementation of the Greek and EU biosafety legislation. This emphasize the urgency of addressing critical gaps in biosafety and in emergency preparedness in Greek biomedical laboratories. Therefore a Biorisk Management System, risk assessments, SOPs, assignment of a Biosafety Officer, staff trainings and emergency response plans should be developed, applied and enforced, in compliance with the local and European legislation and guidelines.